Standard of Transitional Services Provided to Students with Autism Spectrum Disorder from Their Teachers’ Point of View - Mukhtar, Frah Ekram; Ghraib, Reem Mahmoud (Journal of Educational and Psychological Sciences, 2022)
This study aims to identify the standard of transitional services provided to students with Autism Spectrum Disorder (ASD), from the point of view of their teachers, using the analytical descriptive approach. The researchers developed a scale of (6) dimensions, with a high validity and reliability, applied to a sample of (138) teachers of students with (ASD), in public schools and private schools approved in the educational voucher program in Jeddah area. The results showed that the standard of transitional services provided to students with ASD, based on their teachers’ point of view, were at a high rate and the level of challenges in providing transitional services to these students in educational institutions, was also high from the point of view of their teachers. On the other hand the results showed no statistically significant differences in the standard of transitional services provided to the teachers of students with ASD attributable to educational institution, scientific qualification, and the number of years of experience variables. The researchers recommended that transitional service teachers be assigned a workshop, taking into account how to assess performance of students to receive transitional services, as well as prepare, implement and evaluate transitional plans to develop their professional performance.